I Wasn’t at War With the Noise: How Mindfulness Based Cognitive Therapy Changes Patients’ Experiences of Tinnitus - Marks, Elizabeth; Smith, Paula; McKenna, Laurence (Frontiers in Psychology, 2020)
Objectives Intrusive tinnitus is a challenging, life-changing experience for which traditional medical treatment does not yet have a cure. However, Mindfulness Based Cognitive Therapy for tinnitus (MBCT-t) is effective in reducing tinnitus-related distress, disability and intrusiveness. It is a priority to understand patients’ experience of MBCT-t and active processes which they regarded as underpinning the changes they experienced. Semi-structured interviews were conducted 6 months after participants had completed MBCT as part of a randomized controlled trial (RCT), with a focus on exploring their experiences of the course, what they felt had changed and how they felt such changes had occurred. Methods Nine participants took part and Interpretative Phenomenological Analysis (IPA) was used to analyze the interview transcripts. Results Four overarching themes emerged: (1) Relating to Tinnitus in a New Way, (2) Holistic Benefits, (3) Connection, Kindness and Compassion, and (4) Factors Supporting Engagement and Change. Conclusion All participants reported benefits from MBCT-t, based on a radically new relationship with tinnitus. It was no longer characterized by “fighting it” and was instead based on “allowing” tinnitus to be present. Changes were supported by the development of open, stable, present-moment awareness and attitudes of equanimity, kindness, and compassion. Practices encouraging focus on sound (including tinnitus) were challenging, but essential to learning this new way of being with tinnitus. MBCT-t had a huge range of benefits including reduced distress and enhanced wellbeing. The group nature of MBCT-t was an integral part of the therapeutic process. A number of clinical and research implications are discussed.